EGFR-targeted immunoliposomes efficiently deliver docetaxel to prostate cancer cells - Eloy, Josimar O. (2020)
Prostate cancer is the second cause of cancer death in men worldwide. Docetaxel (DTX), an antimitotic drug, is widely used for the treatment of metastatic prostate cancer patients. Taxotere® is a commercial DTX formulation. It contains a polysorbate 80 surfactant to improve DTX aqueous solubility, which has been associated with hypersensitivity reactions in patients. Liposomes have been used as promising delivery systems for a range of hydrophobic drugs, such as DTX, offering improved drug water solubility and biocompatibility, without compromising its anticancer activity. Herein, DTX-loaded liposomes were developed using the Box-Behnken factorial design. The optimized formulation was nano-sized, homogenous in size (67.47 nm) with high DTX encapsulation efficiency (99.95 %). The encapsulated DTX was in a soluble amorphous state, which was slowly released. Next, to increase the liposomes selectivity to prostate cancer cells, cetuximab, an anti-EGFR monoclonal antibody. was successfully conjugated to the surface of liposomes, without compromising cetuximab protein structure and stability. As expected, our results showed higher cellular uptake and toxicity of immunoliposomes, compared to non-targeted liposomes, in DU145 (EGFR-overxpressing) prostate cancer cells. To the best of our knowledge, this is the first report of engineering EGFR-targeted liposomes to enhance the selectivity of DTX delivery to EGFR-positive prostate cancer cells.